The Relationship Between The Quality of Education and The Performance of Lecturers In Waqf-Based Private Universities in West Java - Warizal, Warizal; Gursida, Hari; Sasongko, Hendro (Riviera Publishing, 2023)
The current top priority for an educational institution is to improve the quality of instruction. The key component in creating sustainable education is this. The effectiveness of lecturers is one factor that impacts educational quality. This study examines the connection between lecturer performance and educational quality at private West Javan universities with a waqf foundation. This study is a quantitative explanatory study. At private West Javan universities with a waqf foundation, 113 lecturers were randomly chosen to participate in the survey. On a scale of 1 to 5, respondents were asked to complete an online questionnaire. The Pearson product-moment correlation test was used to examine the acquired data to determine whether there was a relationship between the variables and how strong that relationship was. The findings revealed that for the variable quality of instruction and teacher performance, the Pearson correlation (r count) was 0.680 with a significance level of 0.000. The estimated value for r, which is 0.176, is higher than the number from the r table. Variables have created a strong and favorable association with one another. Conclusion: The professors perform better when the quality of the education is higher.